Perilaku Model Peran Profesional dalam Pendidikan Keperawatan Indonesia - Christie Lidya Rumerung; Ni Gusti Ayu Eka; Peggy Sara Tahulending (Universitas Malahayati Lampung, 2022)
ABSTRACT Professionalism in nursing is constantly changing because of the nursing professional development and the values of the community. One important step in achieving and maintaining professionalism in nursing education is through Role modelling. This study was to identify professional role modelling behaviour in nursing education settings from the perspective of the students at a private faculty of nursing in Indonesia. This study applied an exploratory sequential with a mixed-method design that collected qualitative and quantitative data within two different phases. In the first phase, qualitative data were collected via open-ended questions from a total of 287 students. The qualitative data was analysed using thematic analysis which then developed into a quantitative research questionnaire. The newly developed questionnaire was tested for its validity and reliability to 30 students (Cronbach Alpha 0.97). In the second phase, the 35 item questionnaire was developed and self-administered to undergraduate nursing students. Respondents provided opinions on a four point scale (strongly disagree, disagree, agree, and strongly agree). A descriptive statistic was used to describe its item of the questionnaire. Total of 263 nursing students agreed to involve in the study. First Phase reveald categories of professional role modelling in nursing consist of guiding, willing to help, smart, caring, have love, commitment, competence, integrity and have the character of Christ, patient, disciplined. These categories were then developed into a role model questionnaire consisting of 35 questions. Second phase using the questionnaire most students (80%) agreed that nurse educators demonstrated professional role modelling behaviour in nursing education settings. However, few students disagreed, indicating that they witnessed unprofessional behaviour in their learning journey. This study has developed a number of characteristics of professional role modelling in nursing education settings that most students have agreed. These characteristics are essential and desirable for role models so they could assist nurse educators to strengthen needed characteristics within their institutions. Keywords: Professional, Role Modelling, Nurses